Antibiofilm effect of Nano chitosan and calcium hydroxide intracanal medications and their effects on the microhardness and chemical structure of radicular dentine - Maha Nasr; Ahmed Abdou; Dina M. Bassiouny; Reham Hassan (BMC Oral Health)
Abstract Background Disinfection of the root canal system is a challenge to all clinicians, calcium hydroxide Ca(OH)2, one of the most popular intracanal medications used for this purpose, has some unwanted effects on dentine. This study aimed to investigate the antibiofilm effect of Nanochitosan (CSNPs) and Calcium hydroxide Ca(OH)2 intra canal medications and their effect on the microhardness and chemical structure of radicular dentine. Methodology A total of 52 extracted human mandibular premolars were used. Eighteen premolars were instrumented, sterilized, and inoculated with Enterococcus faecalis ( E. faecalis) then divided randomly into 2 groups based on the intracanal medication used: group (A) 2% CSNPs gel and group (B) Ca(OH)2 paste. Antibiofilm effect was evaluated using bacterial counts. For the effect on microhardness, 56 specimens were subjected to Vicker’s microhardness test before and after 1 week, and 4 weeks of medication application. Twelve cervical radicular dentine specimens (6 samples per group) were examined using Fourier transform infrared spectroscopy and scanning electron microscope. Results Both groups showed a significant reduction in the bacterial count at (p = 0.008) with no significant difference between them (P = 0.605). Ca(OH)2 showed the highest reduction in the microhardness compared to CSNPs groups after 1 week (P = 0.0495) and after 4 weeks (P = 0.0495). FTIR spectrum results revealed that the control group (no treatment) showed the highest significant Phosphate: amide ratio compared to both CSNPs and Ca(OH)2 at p = 0.006. SEM images revealed absence of discernible smear layer in CSNPs treated samples after 4 weeks and all the dentinal tubules were open. Conclusions Nanochitosan gel could be considered as a viable option as an intra canal medication.